Processed multichannel seismic data along the Southeast Indian Ridge, acquired during the R/V Maurice Ewing survey EW0114 (2001) (IEDA: Marine-Geo Digital Library, 2019)
This cruise along the Southeast Indian Ridge collected both MCS and OBH data in order to investigate the effects of temperature variations on magma supply and the crustal accretion process. The objectives were to determine the internal structure of the crust, particularly Layer 2A (extrusive) thickness and its relationship both to melt supply and to axial and abyssal hill crustal structure and to axial and ridge flank morphology, in order to better understand the crustal accretion process. Funded by NSF grant OCE99-11720.